Towards the integration of engagement and engineering‐level simulation over real‐time and heterogeneous systems‡. (21st March 2016) - Xu, Xiao; Li, Ge; Yang, Mei; Ju, Rusheng; Huang, Kedi
Summary: In the context of the joint simulation of engagement and engineering level for weapon system evaluation, engineering models provide precise performance data to support engagement models obtaining more reliable effectiveness results. This paper presents our practice in constructing a synthetic warship anti‐air weapon system simulation platform, which aims to integrate one digital system at engagement level and three hardware‐in‐the‐loop systems at engineering level. Interoperation and real‐time constraints satisfaction are two important issues that we concern. Our approach is to propose a three‐tier hierarchical integration architecture to organize different data flows according to their timing constraints. The architecture assigns each system a proxy to make them mutually compatible. The proxy also provides necessary services to support their joint simulation. Particularly, we adopt a GPS‐based approach to achieve the time synchronization. We also made evaluations on the architecture's performance as well as our integration work. Results show that the two‐level joint simulation could be effectively addressed under our proposed architecture. Copyright © 2016 John Wiley & Sons, Ltd.